Performance Analysis of Dual Fuel Diesel Generator with Variations in LPG Flow Rate and Air Hole Diameter - Witanto, Y; Amsah, I; Zukri, D; Nuramal, A; Rosa, M.K.A. (Universitas Muhammadiyah Jakarta, 2023)
Research on dual fuel diesel engines has been the main focus, but research on the composition of LPG and air in the intake manifold is still limited. This study aims to analyze the performance of a dual fuel diesel generator set by varying the LPG flow rate and air hole diameter in the intake manifold. The research method applied is experimental with test variables in the form of gas flow rate (1 LPM, 2 LPM, and 3 LPM) and air hole diameter (19 mm, 21 mm, 23 mm, 25 mm, and 27 mm). These test variables significantly affect electrical power and SFC (Specific Fuel Consumption). Analysis was conducted using single factor Anova. The results showed that the addition of LPG gas with variations in flow rate resulted in an increase in power compared to the use of pure diesel, especially at high loads. A significant increase in power occurred at an orifice diameter of 27 mm at an LPG flow rate of 3 LPM, reaching 1548 Watts. The SFC shows that the addition of LPG substituted with diesel is more efficient and effective than using only diesel. The lowest SFC occurred in the variation with an LPG gas flow rate of 1 LPM, at an air hole diameter of 25 mm, which amounted to 0.002721 kg/kWh. In conclusion, this study illustrates the impact of variations in LPG flow rate and air outlet diameter on the performance of dual fuel diesel gensets. The implications of these findings can support the development of more efficient and environmentally friendly engine technology.